Different piezoelectric grain size effects in BaTiO3 ceramics. Issue 10 (December 2015) - Wang, J.C.; Zheng, P.; Yin, R.Q.; Zheng, L.M.; Du, J.; Zheng, L.; Deng, J.X.; Song, K.X.; Qin, H.B.
Abstract: Four groups of barium titanate (BaTiO3 ) ceramics with high piezoelectric coefficient have been successfully fabricated from different raw materials. Their average grain size ( g ) dependences of the piezoelectric coefficient d 33 were systematically studied. It was found that for two groups of BaTiO3 ceramics, d 33 firstly increases and then decreases with the increase of g, with a maximum d 33 of 449 pC/N and 501 pC/N respectively at approximately 1 µm grain size, while for the other two groups of BaTiO3 ceramics, d 33 keeps increasing with the increase of g . The highest d 33 of 401 pC/N and 424 pC/N were obtained when g is larger than 50 µm. The experimental results indicated that piezoelectric grain size effect in BaTiO3 ceramics may be not absolute. Possible mechanisms arising from differences in domain configuration were discussed.